Sustainable Management: A Bibliometric Review of Current Trend and Development - Nelson Lajuni; Yusman Yacob; Salumah Nain; Jati Kasuma (Majmuah Enterprise, 2020)
With environmental issues such as global change, pollution and depletion of natural resources impacting human dailylife, businesses need to learn how to mitigate, reuse and recycle to conserve our environment whilst caring abouthuman beings andoptimising benefits. Sustainable management looks above short-term quarterly profits and focuseson long-term advantages by incorporating sustainability issues into management decisions. Therefore, trends in globalresearch on this topicisbeen analyzed and studiedusinga bibliometric review on current trend and development of‘sustainable management’ over28years (1992-2020) on topics related to business, economics and accountingandEconomics, Econometrics and Finance.By adopting bibliometric analysis, we derived data from Scopus onlinedatabase as of December 13, 2020. Based on the ‘keywords’ search results, our study finalised 1,065valid documentsfor further assessments. We utilised Harzing’s Publish and Perish to analyse basic evaluations before proceeding withVOSviewer for data visualisation purposes. The findings highlight the trend of literature on ‘sustainable management’since its inception in 1992until today. The number of publications achieved 100 publications since 2018and keptincreasing each year. Most previous publications were in English, with more than 164authors from more than117different countries. Using specific keywords of ‘sustainable management’, the results were derived based on the titlesand keywords of the documents. Thus, the results of the search query for other fields such as abstracts, and differentkeywords are excluded. This paper offers an overview and better understanding of the current trends and developmentof the topic since its inception over28years, and also serve as a valuable reference for future research.